2018
DOI: 10.1002/jez.2169
|View full text |Cite
|
Sign up to set email alerts
|

Nesting environment may drive variation in eggshell structure and egg characteristics in the Testudinata

Abstract: Testudines exhibit considerable variation in the degree of eggshell calcification, which affects eggshell conductance, water physiology of the embryos, and calcium metabolism of embryos. However, the underlying reason for different shell types has not been explored. Phylogenetically controlled analyses examined relationships between egg size, shell mass, and clutch size in ∼200 turtle species from a range of body sizes and assigned by family as laying either rigid- or pliable-shelled eggs. Shell type affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…We also observed that eggshells had an ornamentation, made up of columnar structures, some of them joined by bridges (Fig. 2 ), depending both on erosion by external factors during incubation and on the characteristics of the nest itself 6 , 7 , 16 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We also observed that eggshells had an ornamentation, made up of columnar structures, some of them joined by bridges (Fig. 2 ), depending both on erosion by external factors during incubation and on the characteristics of the nest itself 6 , 7 , 16 .…”
Section: Discussionmentioning
confidence: 75%
“…Temperature in the nest may affects the rate of calcium mobilization. The mobilization of calcium is not only from eggshell, but also from yolk, varying the proportion of consumption according to the species, with crocodiles and birds consuming more calcium from eggshell; and some snakes consuming more from yolk 4 , 16 . Studies on Alligator mississippiensis reveal that during the third week of incubation there is a reduction in the small calcium crystals in eggshell, which appear to be mobilized in the embryo calcification 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Different eggshell types may provide different levels of protection to embryos (Deeming, 2018). The rigid cased P. unifilis eggshells may help to explain the resistance of embryos to short-term submersion (Packard, Packard & Boardman, 1982;Winkler, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Different eggshell types may provide different levels of protection to embryos (Deeming 2018). The rigid cased P. unifilis eggshells may help to explain the resistance of embryos to short-term submersion (Packard et al 1982;Winkler 2006).…”
Section: Discussionmentioning
confidence: 99%